2010
DOI: 10.2214/ajr.09.2763
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Vascular Manifestations of Behçet Disease: Imaging Findings

Abstract: CT is a valuable imaging technique in the diagnostic work-up of Behçet disease. CT effectively demonstrates vascular system involvement that is the main cause of mortality in these patients. CT is also effective in detecting mediastinal, pleural, and pulmonary parenchymal findings related to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 14 publications
1
72
0
17
Order By: Relevance
“…Venous occlusion is most frequently seen at the level of superior vena cava. 35 In the current study, the serum MDA level was found to be significantly increased in patients with BD than healthy controls. This result may indicate an active role of ROS in the pathogenesis of BD.…”
supporting
confidence: 48%
“…Venous occlusion is most frequently seen at the level of superior vena cava. 35 In the current study, the serum MDA level was found to be significantly increased in patients with BD than healthy controls. This result may indicate an active role of ROS in the pathogenesis of BD.…”
supporting
confidence: 48%
“…Similarly, Hughes-stovin syndrome (HSS), a close differential of BD with consistent radiologic and histopathologic finding was unlikely as our patient had both oral and genital ulcer which are usually absent in HSS [13]. Patient could have been managed as smear negative tuberculosis in a high burden country but for the rapid and sensitive diagnostic test of Xpert MTB/RIF test which was also negative.…”
Section: Discussionmentioning
confidence: 75%
“…4) Vascular system involvement is significantly more common in men than women, seen in approximately 25%-30% of patients and is the most common cause of mortality. 5) Vascular lesions are classified into three types: arterial occlusions, arterial aneurysms, and venous thromboses. The most common manifestation of vascular involvement in Behcet's disease is Venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%